2007
DOI: 10.1002/bjs.6008
|View full text |Cite
|
Sign up to set email alerts
|

Mode of splenectomy and immunogenicity of meningococcal vaccination in patients with hereditary spherocytosis

Abstract: Near-total splenectomy provides a favourable immunological basis for natural and vaccine-induced protection against meningococcal serogroup A and C infections. Sequential meningococcal vaccination is immunogenic in patients splenectomized for hereditary spherocytosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…In addition, several authors have reported an association between asplenic patients and pulmonary hypertension, suggesting that chronic thromboembolic events may lead to significant compromise of pulmonary function [5][6][7]. Other concerns for splenectomized patients include studies suggesting increased risk of atherosclerosis, incomplete immunization with current vaccines [8][9][10][11], and noncompliance with antibiotic prophylaxis regimens, particularly as children enter adolescence and adulthood.…”
mentioning
confidence: 94%
“…In addition, several authors have reported an association between asplenic patients and pulmonary hypertension, suggesting that chronic thromboembolic events may lead to significant compromise of pulmonary function [5][6][7]. Other concerns for splenectomized patients include studies suggesting increased risk of atherosclerosis, incomplete immunization with current vaccines [8][9][10][11], and noncompliance with antibiotic prophylaxis regimens, particularly as children enter adolescence and adulthood.…”
mentioning
confidence: 94%
“…Given that the mortality rate associated with OPSI is 40-70% [2], immunisation against encapsulated bacteria is mandatory [3]. Prior to the advent of pneumococcal conjugate (PCV7), meningococcal conjugate (MCV4) and Hib vaccines, post-splenectomy septic mortality rate was reported as between 0.073 and 0.1/100 person-years [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…There is no clear correlation that the volume of splenic regrowth or splenosis offers immune protection, and preliminary findings exacerbate this risk as immune protection declines with age independent of splenectomy . The immunogenic response to pneumococci and meningococci vaccination is also less than ideal following splenectomy performed for congenital hemolytic disorders . These scanty data support the extra concern noted in a recent review of vaccination guidelines for the care of hyposplenic individuals .…”
Section: Discussionmentioning
confidence: 93%